PENGARUH MENGKONSUMSI LARUTAN PROPOLIS TERHADAP PH SALIVA - Sariyem ,; Sadimin ,; Rufaida Poppy Yuwana (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2014)
ABSTRACT Rinsing solution of propolis is one of the traditional treatment efforts, to preserve and maintain oral health. Propolis contains flavonoids that have a bitter taste. Bitter taste indicates if propolis propolis has alkaline and can neutralize the acid. The purpose of this study was to determine the effect of consuming solution of propolis on salivary pH.This type of research was quasi-experimental. The research design was a pretest-posttest used the Control Group Design. The population in this study were all first year students of Nursing Department of Dental Health Polytechnic Semarang some 148 people. And large samples taken using the formula Federer, from the formulas obtained a sample of 20 students who were divided into two groups: the experimental group consumed a solution of propolis treatment and control group with distilled water consuming treatment. How to study the samples are given instruction brushing and diet foods one hour before treatment. Taking the pH of saliva before and after treatment. This study used a paired samples t-test and independent samplet-testusingSPSS.The results showed that an increase in the pH of saliva after eating propolis solution at 0.44 and there is also an increase in the pH of saliva after consuming distilled water at 0.62. Based on the paired samples t-test with a confidence level of 95%, the results obtained in the control group with p = 0.001, for p 0.05 means that there is the influence of consuming distilled water to a pH of saliva. And also the results obtained in the experimental group with p = 0.021, for p 0.05, then Ho is rejected and Ha accepted, meaning that there is a solution to consume the influence of propolis on the pH of saliva. However, from the results of independent t-test trials showed no difference consume propolis solution and distilled water to a pH of saliva. Key words : Propolis solution,the pH of saliva